Macrostructural Performance of Binary Blend Self-Compacting Concrete (SCC) Containing Calcined Eggshell and Silica Fume Exposed to Elevated Temperature - Sobri, Nur Syazwani; Md Zain, Mohd Raizamzamani; Rahman, Mohd Khairil; Oh , Chai Lian; Lee, Siong Wee (International Journal of Integrated Engineering, 2025)
Concrete, as a main material in the construction sector, has been essential for global advancement. Traditional cement production, a crucial component of concrete, contributes significantly to environmental challenges, particularly CO₂ emissions, which are a major concern in efforts to mitigate climate change. In addition, typical concrete frequently presents issues such as low workability and poor performance during handling and placing. While advancement has been made by combining sustainable resources, the potential for self-compacting concrete (SCC) using Calcined Eggshell Powder (CESP) and silica fume (SF) as a sustainable alternative remains underexplored. The present study addresses the urgent demand for environmentally friendly and high-performance concrete by assessing the fresh and macrostructural properties of SCC with CESP and silica fume (SF) as partial cement substitutes, particularly at elevated temperatures. Fresh properties tests, such as Slump Flow, T500, and Sieve Segregation, were used to evaluate the flowability and stability of SCC mixes, while macrostructural properties testing was used to measured compressive and split tensile strengths. SCC mixes were produced with varying CESP content (0%, 5%, 10%, and 15%) and 10% SF as partial cement replacements. Compressive strength was evaluated using 100x100x100 mm cubes, whereas split tensile strength was determined utilizing 50 mm diameter × 100 mm height cylinders. The experimental results revealed that all SCC combinations met or exceeded the EFNARC 2005 criteria for flowability and segregation resistance, with slump flow values that varied between 555–660 mm (EFNARC limit: 550–850 mm), T500 times between 3.56–5.82 seconds (EFNARC range: 3–6 seconds), and sieve segregation ratio of 5.67–11 % (EFNARC limit: ≤15 %). The compressive and split tensile strengths met critical threshold of 30 MPa and 2 MPa, respectively, confirming the practicality of the proposed mix designs. Additionally, the CE5S10 mix achieved optimal performance with compressive and split tensile strengths of 28.24 MPa and 2.67 MPa, respectively. Failure modes exhibited diverse fracture patterns, including edge cracks in compressive samples and horizontal center cracks in tensile specimens. A linear relationship was discovered between compressive and split tensile strengths, implying a forecasting potential for material performance. The study’s findings emphasize the innovative potential of incorporating calcined eggshell powder and silica fume into SCC, which provides an additional benefit of lowering the usage of cement while also reusing waste materials. This research not only adds to the development of more sustainable construction practices, but it also fills crucial gaps in understanding the performance of sustainable concrete at elevated temperatures. The findings lead to a path for widespread adoption of eco-friendly SCC formulations, which aligns with global initiatives to reduce environmental impacts and promote principles of the circular economy in the construction sector.